Kemandirian Pangan Melalui Optimalisasi Lahan Pekarangan - Setiawan, Agus Nugroho; Wijayanti, Septi Nur (Universitas Muhammadiyah Yogyakarta, 2020)
Food independence is an effort to fulfill the need of food for a family by themselves. The fulfillment effort of family need for food in independent way can be done on a limited land around the house, known as yard. Developing the yard for food plant becomes very important, regarding the fast conversion of food plant land into the non- food one. This phenomenon took place in Ngemplak Hamlet, Kembangarum, Donokerto, Turi, Sleman. There were many food plant lands in this area conversed into lands for salak pondoh (a type of snake fruit). So, yard optimization can be done by house wives joining in Family Welfare Program (PKK) who have spare time at home, because it is located around the house. The society empowerment in this program is conducted with methods or stages of socialization, technology transfer education (training, demonstration, and practice), and supervision as well as evaluation through the guidance for the program sustainability. The success of the society empowerment program is shown by the active participation of the society, the increase of the knowledge and skills of the PKK women, as well as the increase of land use of the society by cultivating vegetable and fruit.